2014
DOI: 10.1002/ppsc.201300383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rod‐Shaped Nanoparticles as Carriers for Gene Delivery

Abstract: Fabrication of nonspherical particles for gene delivery remains a major challenge. In this study, novel rod-like nanoparticles are prepared for effi cient gene delivery by self-assembly of α-cyclodextrin (α-CD) and polyethyleniminemethoxy poly(ethylene glycol) (PEI-mPEG). The study reveals that the rod-like PEI-mPEG/α-CD particles can bind DNA effectively and the resulting PEImPEG/α-CD/DNA complexes show over four times higher gene delivery capability than their spherical counterparts and PEI(25K) due to more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…5,6 Therefore, various rod-like nanoparticles have been prepared using liposomes, peptides, polylactide (PLA), chitosan, and other polymers. [7][8][9][10] Among them, PLAs have attracted considerable attention, due to the fact that they are synthesized from renewable resources and are nontoxic aer biodegradation, for various applications in industry, agriculture, and biomedical elds. 11,12 Up to now, many researchers have reported the preparation of nanoparticles, nanobers and nanolms based on PLA.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Therefore, various rod-like nanoparticles have been prepared using liposomes, peptides, polylactide (PLA), chitosan, and other polymers. [7][8][9][10] Among them, PLAs have attracted considerable attention, due to the fact that they are synthesized from renewable resources and are nontoxic aer biodegradation, for various applications in industry, agriculture, and biomedical elds. 11,12 Up to now, many researchers have reported the preparation of nanoparticles, nanobers and nanolms based on PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Particle shape influences the cell uptake and the rod‐like nanoparticles are more favorable for drug and gene delivery applications. [ 58,59 ] The shape of the particle strictly impacts on its internalization by macrophage. [ 60,61 ] A recent study suggested that rods are taken up by the cells more rapidly than spherical particles.…”
Section: Resultsmentioning
confidence: 99%
“…Another kind of nanoassembly was rod-like nanoparticles prepared by self-assembly of a-CD and PEG-PEI. 65 The rod-like particles can bind DNA effectively and showed over 4 times higher gene delivery capability than its spherical counterpart and PEI (25 kDa) (Fig. 18).…”
Section: Gene Deliverymentioning
confidence: 99%
“…Fig.18Schematic illustration of the formation of DNA/PEI-PEG/a-CD nanospheres and nanorods for gene delivery 65. …”
mentioning
confidence: 99%